Analisis Nilai Tambah Keripik Nangka pada Agroindustri UD Dua Dewi di Kabupaten Jember - Lilik Laeliyah; Jani Januar (UPT Penerbitan Universitas Jember, 2018)
Jackfruit is one of the horticultural commodities which are included in Floriculture. Jackfruit chips is one of the processed product of jackfruit be jackfruit chips. the product became a superior product at UD Dua Dewi. UD Dua Dewi has an initiative to process jackfruit into jackfruit chips so that provide added value to the jackfruit, have a higher economic value and longer shelf life. The production scale of UD Dua Dewi in one production process produced 5 kg of jackfruit chips from 75 kg of raw material from jackfruit. This study aims to determine: (1) the Value added of the processed product of jackfruit be jackfruit chips on UD Dua Dewi. The method of data collection is done by interviews and field observations to find out the conditions and facts in the field. The sampling method used is Purposive sampling. The tools of analytical used the value added analysis of the Hayami method. The results showed that: Processing of jackfruit into jackfruit chips in agroindustry UD Dua Dewi was classified as giving a medium added value with a value added of 3,100.83 and a ratio of value added is 35.78%.